Neurodevelopment at seven years and parents' feelings of prematurely born children - Mercier, Clémentine; Deforge, Hélène; Hascoët, Jean-Michel (Frontiers in Pediatrics, 2022)
Background: The evolution of knowledge and technical advances in neonatal resuscitation have improved the survival of very premature babies. However, the long-term neurodevelopmental prognosis and cognitive and learning abilities are still uncertain. Objective: This study aimed to evaluate the neurodevelopment and learning abilities of 7-year-old children born prematurely, and their parents’ feelings at 8 years of age. Patients and methods: Data from children born before 33 weeks gestation in a level III maternity hospital and involved in a regional follow-up network were analyzed at 7 years of age. Neurodevelopmental abnormalities were defined as cerebral palsy, hearing or visual impairment, and/or behavioral abnormalities. School performance was evaluated by the EDA test. A parents’ questionnaire assessed their feelings about the child’s and family’s quality of life at 8 years of age. Results: At 7 years of age, 51% of the 238 children presented neurodevelopmental abnormalities: 3.3% with cerebral palsy, 6.2% with hearing impairments, 50.7% with visual impairments, and 11.3% with behavioral disorders. The children with neurodevelopmental abnormalities had lower gestational age (29.0±2.0 vs. 30.0±2.1 weeks, p=0.003) and more EEG abnormalities during the neonatal period (31.1% vs. 19.8%, p=0.048) than the children without abnormalities. Ninety-four percent of the children with abnormalities were enrolled in normal schools, 33% with special support. In the overall cohort, 31% of the children had all academic performance scores in the normal range of the reference population. At 8 years old, 39% of the parents of children with neurodevelopmental abnormalities felt that their child’s situation significantly impacted their quality of life compared to 14% of parents of children without neurodevelopmental abnormality (p=0.022). Conclusion: Half of children born very prematurely present with long-term neurodevelopmental abnormalities, which their parents feel significantly impacts their quality of life.